Sex differences in the neuronal transcriptome and synaptic mitochondrial function in the cerebral cortex of a multiple sclerosis model - Itoh, Noriko; Itoh, Yuichiro; Stiles, Linsey; Voskuhl, Rhonda (Frontiers in Neurology, 2023)
Multiple sclerosis (MS) affects the cerebral cortex, inducing cortical atrophy and neuronal and synaptic pathology. Despite the fact that women are more susceptible to getting MS, men with MS have worse disability progression. Here, we address sex differences in neurodegenerative mechanisms focusing on the cerebral cortex using the MS model, chronic experimental autoimmune encephalomyelitis (EAE). RNA sequencing of neurons in cerebral cortex during EAE showed robust differential gene expression in male EAE mice compared to male healthy, age-matched, control mice. In contrast, there were few differences in female EAE mice compared to female controls. The most enriched differential gene expression pathways in male mice during EAE were mitochondrial dysfunction and oxidative phosphorylation. Mitochondrial morphology showed significant abnormalities in the cerebral cortex of EAE males, but not EAE females. Regarding function, synaptosomes isolated from cerebral cortex of male EAE mice demonstrated decreased oxygen consumption rates during respirometry assays. Together, cortical neuronal transcriptomics, mitochondrial morphology, and functional respirometry assays in synaptosomes revealed worse neurodegeneration in male EAE mice. This is consistent with worse neurodegeneration in MS men and reveals a model and a target to develop treatments to prevent cortical neurodegeneration and mitigate disability progression in MS men.